2001
DOI: 10.1073/pnas.98.3.1083
|View full text |Cite
|
Sign up to set email alerts
|

Extrafloral nectar production of the ant-associated plant,Macaranga tanarius,is an induced, indirect, defensive response elicited by jasmonic acid

Abstract: Plant species in at least 66 families produce extrafloral nectar (EFN) on their leaves or shoots and therewith attract predators and parasitoids, such as ants and wasps, which in turn defend them against herbivores. We investigated whether EFN secretion is induced by herbivory and͞or artificial damage, and thus can be regarded as an induced defensive response. In addition, we studied the underlying signaling pathway. EFN secretion by field-grown Macaranga tanarius increased after herbivory, artificial leaf dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(173 citation statements)
references
References 36 publications
8
158
3
4
Order By: Relevance
“…4], a result consistent with earlier observations on lima bean plants exposed to artificial VOCs (31). It is therefore most likely that at least a part of this defensive effect was due to an EFN-mediated increase in ant numbers (27,29,32). …”
Section: Resultssupporting
confidence: 81%
“…4], a result consistent with earlier observations on lima bean plants exposed to artificial VOCs (31). It is therefore most likely that at least a part of this defensive effect was due to an EFN-mediated increase in ant numbers (27,29,32). …”
Section: Resultssupporting
confidence: 81%
“…Some studies show that in certain cases, the EFN secretion can be induced by jasmonic acid (Heil et al 2001), a phytohormone which often increases during fruit development (Lopez et al 1987;Czapski & Saniewski 1992;Creelman & Mullet 1997). In this context, such studies could support our initial hypothesis in which the EFN secretion can be higher in bigger and riper fruits of A. verrucosa.…”
Section: Discussionsupporting
confidence: 77%
“…Numerous studies have found that ant rewards are produced sparingly, which certainly suggests that they are costly to make. For example, Heil et al (2001) and Palmer et al (2008) showed that both domatia and extrafloral nectar production can be induced by herbivory, and plants often produce extrafloral nectar and food bodies on only young, expanding leaves, which are the most vulnerable to folivory (Coley and Barone 1996). However, other previous tests of the costs of ants to plants have been inconclusive (i.e., Rudgers 2004; Rudgers and Strauss 2004;Rutter and Rausher 2004).…”
Section: Costs Of Ant Defense To Cordia Nodosamentioning
confidence: 99%